Downregulation of amyloid precursor protein inhibits neurite outgrowth in vitro (The Rockefeller University Press, 1995)
The amyloid precursor protein (APP) is a transmembrane protein expressed in several cell types. In the nervous system, APP is expressed by glial and neuronal cells, and several lines of evidence suggest that it plays a role in normal and pathological phenomena. To address the question of the actual function of APP in normal developing neurons, we undertook a study aimed at blocking APP expression using antisense oligonucleotides. Oligonucleotide internalization was achieved by linking them to a vector peptide that translocates through biological membranes. This original technique, which is very efficient and gives direct access to the cell cytosol and nucleus, allowed us to work with extracellular oligonucleotide concentrations between 40 and 200 nM. Internalization of antisense oligonucleotides overlapping the origin of translation resulted in a marked but transient decrease in APP neosynthesis that was not observed with the vector peptide alone, or with sense oligonucleotides. Although transient, the decrease in APP neosynthesis was sufficient to provoke a distinct decrease in axon and dendrite outgrowth by embryonic cortical neurons developing in vitro. The latter decrease was not accompanied by changes in the spreading of the cell bodies. A single exposure to coupled antisense oligonucleotides at the onset of the culture was sufficient to produce significant morphological effects 6, 18, and 24 h later, but by 42 h, there were no remaining significant morphologic changes. This report thus demonstrates that amyloid precursor protein plays an important function in the morphological differentiation of cortical neurons in primary culture.